The ancient egyptian roots of the image of the panther in the alexandrian Physiologus - Eleonora Kormysheva (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология)
The purpose of this study is to trace the Old Egyptian roots of the Panther’s figure, symbolising the Saviour in the zoological mystery play Physiologus created in Egyptian Alexandria. Taking into account the opinion expressed in the literature about the loss of the predator’s features in the Panther and its transformation in the Physiologus into a sexless image, this article draws on textual and visual material and traces those characteristic features of the Panther in ancient Egyptian mythology which remained inherent in its image in the Physiologus. In order to accomplish this task, the article demonstrates the following features of its image which, as the author argues, go back to the Old Egyptian tradition. This is the initial unity of the Panther and the Serpent, which is seen in early monuments of the Old Egyptian culture, i.e. the palettes of the Early Dynastic period from Hierakonpolis, where one can observe a combined image depicting the unity of both animals. According to the surviving sources, their rupture and hostility, as well as the transformation of the Panther into a defender of the Sun God, are refl ected in the Pyramids Texts of the Old Kingdom (III millenium B.C.), where the female Panther, Mafdet, acts. She kills the Serpent, who is an enemy of the Sun God. The article also studies the Egyptian roots of the ideas about the Panther’s multicolouredness, refl ected in the Physiologus. The article cites data related to the attitude of the Egyptians to the skin of the Panther as a personalised model of cosmos. An example is the apparel of the priests and of the deceased in front of the sacrificial table, as well as the head of the Panther on various objects, e.g. attire items, magic wands. Besides, the formation of the image of the Panther as a zoological personification of the Saviour was arguably infl uenced by her role as a carrier of souls of the dead in the other world. To support this view, the magic wands of the Middle Kingdom are studied, on which are depicted the mythical images of a winged Panther with the head of a falcon, the carrier of the head of the deceased, as well as the fi gures of Tutankhamun riding on a black Panther, which were found in his sepulchre. Arguably, the Panther’s features as the protector of the Sun God and the transformer of the souls of the other world had led to its personifi cation in the image of Christ.